2018
DOI: 10.1002/adma.201706157
|View full text |Cite
|
Sign up to set email alerts
|

Printable Superelastic Conductors with Extreme Stretchability and Robust Cycling Endurance Enabled by Liquid‐Metal Particles

Abstract: Stretchable conductors are vital and indispensable components in soft electronic systems. The development for stretchable conductors has been highly motivated with different approaches established to address the dilemma in the conductivity and stretchability trade-offs to some extent. Here, a new strategy to achieve superelastic conductors with high conductivity and stable electrical performance under stretching is reported. It is demonstrated that by electrically anchoring conductive fillers with eutectic gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
268
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(269 citation statements)
references
References 38 publications
1
268
0
Order By: Relevance
“…f) Electrical response of the 3D vial integrated with the touch sensor. Reproduced with permission . Copyright 2018, John Wiley and Sons.…”
Section: Applications Of Liquid Metal–based Microfluidic Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…f) Electrical response of the 3D vial integrated with the touch sensor. Reproduced with permission . Copyright 2018, John Wiley and Sons.…”
Section: Applications Of Liquid Metal–based Microfluidic Systemsmentioning
confidence: 99%
“…Further, Lee et al reported a stretchable conductor filled with conductive fillers (such as Ag flakes) and EGaIn particles with superelasticity. The composite can be patterned on an arbitrary substrate and even on 3D curved surfaces (such as glass vial) (Figure d).…”
Section: Applications Of Liquid Metal–based Microfluidic Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…An additional challenge for fabricating fully stretchable OECTs is that they require stretchable metal contacts. Stretchable conductors such as liquid metals, although increasingly used in stretchable electronics, are not suitable as electrodes for OECTs due to their limited electrochemical stability and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%